Policy Analysis in Thailand - Akarapongpisak, Nattakant; Ariyasirichot, Wachirawat; Aunphattanasilp, Chumphol; Boossabong, Piyapong; Boossabong, Piyapong; Buddharaksa, Watcharabon; Chaichakan, Chatthip; Chaiyapa, Warathida; Chamchong, Pobsook; Chattragul, Phanuphat; Chutima, Vorapat; Geva-May, Iris; et al. (International Library of Policy Analysis, 2023)
The subject of policy analysis in Thailand is less examined than in Western societies. This is the first English language book to engage in a detailed, comprehensive and current study of policy analysis in Thailand. Providing a broad view of the history, styles and methods of policy analysis in Thailand, it examines policy analysis both within and beyond executive government, revealing the role of parties, military, and interest groups. It will be a valuable resource for policy analysis researchers and practitioners and as a comparison with other volumes in the International Library of Policy Analysis series.